Tindak Tutur Dalam Wacana Iklan Berbahasa Indonesia Di Televisi: Sebuah Kajian Pragmatik - ANJANI, YUNI, Drs. H. Yakub Nasucha, M.Hum (2016)
Every advertisement have influence energy with type which different each other, so that have implicit meaning and also letter meaning which is different also. Therefore, this research is done/conducted by under colour of analysing to act to say advertisement discourse have indonesia Ianguage to in television. This research is including pragmatic research type, there is 3 type act to say, locution, ilokusi, and perlokusi. There is 2 Target in this research 1. knowing form act to say to have indonesia Ianguage in television 2. knowing implicit meaning and advertisement Ianguage letter meaning in television. This research is including descriptive research type qualitative. Material at this research counted 10 materials, 10 the advertisement material in ascertaining consumer advertisement type, technique intake of this material pass/through documentation technique, there is three way of documentation technique, technique correct reading, record, and note. Authenticity of material in research with reference materials, existence of supporter to prove data which have been found by researcher. Reference materials in the form of advertisement video from youtube.com. Source of advertisement obtained to pass/through television. As for used technique, by interaktif and take place continuously till saturated material. Result of analysis at advertisement discourse in television counted 10 data, please conclude that the overall of data contain three type act to say locution, ilokusi, and perlokusi. Found to act to say informative locution counted 5 materials, narrative locution counted 4 materials, and descriptive locution counted 2 materials, asertif ilokusi counted 6 materials, ekpresif ilokusi counted 6 materials, perlokusi counted 10 materials. Third of type act to say this is influencing each other. Most message of letter at advertisement submitted/sent informatively, that most advertisement present discourse which do not directly formulate its purposes and objectives. While implicit meaning at this advertisement discourse of a more regular submitted/sent by for the purpose of asking for and ordering.